State security and individual security as exemplified by operational surveillance used by the Polish counter-intelligence service - Rosicki, Remigiusz (Wydział Nauk Politycznych i Dziennikarstwa UAM, 2021)
The material scope of the research problem presented in the text encompasses the issues concerned with operational surveillance that the Polish civilian counter-intelligence service, i.e. the Internal Security Agency (in Polish abbreviated as ABW – Agencja Bezpieczeństwa Wewnętrznego), is authorised to. The main purpose of the analysis is to assess the changes introduced as a result of the passing of the so-called Surveillance Act in 2016. The Act was supposed to introduce new regulations with regard to the powers concerning operational surveillance and obtaining of ICT data, granted to particular secret and police services. The said changes were enforced by the judgment of the Constitutional Tribunal, which in 2014 found numerous violations of the provisions of the Constitutions of the Republic of Poland caused by the existing regulations authorising the services to engage in particular operational and investigative actions. In order to elaborate the material scope of the research problem, and to present the conclusions, the following research questions have been presented in the text: Do the legal regulations concerning the powers vested in the Polish civilian counter-intelligence service within operational surveillance infringe individual rights and freedoms (e.g. the right to privacy, protection of personal information, privacy of correspondence), and if so, then to what extent? Functional and pro-constitutional interpretations have been applied to assess the provisions regulating the powers of the Internal Security Agency with regard to operational surveillance and obtaining of ICT data. The functional interpretation focuses on the function of selected legal solutions, whereas the pro-constitutional interpretation focuses on the assessment of legal solutions in the context of the principles of a democratic state ruled by law, as well as human rights and freedoms. As regards the pro-constitutional interpretation, the tool used for assessment is the test of proportionality, i.e. the rule used for interpreting legal norms according to the degree and legitimacy of the interference in individual rights and freedoms.

Zakres przedmiotowy problemu badawczego w tekście obejmuje tematykę kontroli operacyjnej, do której uprawniony jest polski kontrwywiad cywilny, czyli Agencja Bezpieczeństwa Wewnętrznego (pol. skrót: ABW – Agencja Bezpieczeństwa Wewnętrznego). Głównym celem podjętej analizy jest chęć oceny zmian, które dokonano w związku z przyjęciem tzw. Ustawy inwigilacyjnej w 2016 roku. Ustawa ta miała wprowadzić nowe regulacje w zakresie uprawnień dotyczących kontroli operacyjnej i pozyskiwania danych teleinformatycznych poszczególnych służb specjalnych i policyjnych. Zmiany te wymuszane zostały orzeczeniem Trybunału Konstytucyjnego, który w 2014 roku stwierdził liczne naruszenia przepisów Konstytucji RP przez dotychczasowe przepisy uprawniające służby do stosowania poszczególnych czynności operacyjno-rozpoznawczych. W celu uszczegółowienia zakresu przedmiotowego problemu badawczego i prezentacji wniosków końcowych w tekście przedstawiono następujące pytanie badawcze: Czy i w jakim stopniu regulacje prawne dotyczące uprawnień polskiego kontrwywiadu cywilnego w zakresie kontroli operacyjnej naruszają prawa i wolności jednostki (np. prawo do prywatności, ochronę informacji o sobie i tajemnicę korespondencji)? Do oceny przepisów regulujących uprawnienia Agencji Bezpieczeństwa Wewnętrznego w zakresie kontroli operacyjnej i pozyskiwania danych teleinformatycznych wykorzystano interpretację funkcjonalną i prokonstytucyjną. Interpretacja funkcjonalna skupia się na funkcji wybranych rozwiązań prawnych, natomiast interpretacja prokonstytucyjna na ocenie rozwiązań prawnych w kontekście zasad demokratycznego państwa prawa oraz praw i wolności człowieka. W przypadku interpretacji prokonstytucyjnej, narzędziem oceny jest test proporcjonalności, czyli reguła interpretacji norm prawnych wedle stopnia i zasadności ingerencji w prawa i wolności jednostki.
Bezpieczeństwo państwa i bezpieczeństwo jednostki na przykładzie kontroli operacyjnej stosowanej przez polski kontrwywiad
Keywords: secret services; Internal Security Agency; operational and investigative actions; operational surveillance; surveillance; individual rights and freedoms; służby specjalne; Agencja Bezpieczeństwa Wewnętrznego; czynności operacyjno-rozpoznawcze; kontrola operacyjna; inwigilacja; prawa i wolności jednostki